A Contribution Analysis of Tamla Offshore Wind Farm by Using of Probability Simulation Method. Issue 4 (2019) - Jeong, Semin; Oh, Ungjin; Lee, Yeonchan; Choi, Jaeseok
Abstract: This study aims to analyze the reliability of wind power generator in Jeju Island power system in order to maintain the operational state of power system at the reliability levels. It is also described an algorithm for probabilistic production cost credit evaluation of Wind Turbine Generators (WTG). An analysis on generated capacity of wind power generator with Tamla offshore wind farm according to two different average wind speeds such as 11.8 [m/s] and 12.8 [m/s], and without Tamla offshore wind farm have been done in terms of Effective Load Carrying Capability (ELCC) and Capacity Credit (C.C.) in power system from the perspective of Loss of Load Expectation (LOLE). According to the changing of wind speed in the Tamla offshore wind farm, this paper demonstrates how it changes the ELCC and C.C. shown as case studies.